Maribor city region - Drozg, Vladimir (Journal for Geography, 2006)
The first part of this contribution deals with the contents of the term ‘city region’. This is an area, defined by economical and social relationships between the town and its surroundings. Within these parameters, the economical-geographic and socio-geographic characteristics of the city region can be defined. A city region is an area that changes with time and through characteristics which define it. This is also the reason why we cannot define it once and for all. It is also not possible to restrict it with more than one element, because the spatial range of elements varies considerably. The second part of the contribution shows the city region of Maribor. This includes a large part of the north-eastern Slovenia, irrespective of the parameters, one wants to define it with. However, one can establish that the said city region is larger in the social than in the economical sense.